Edukasi Anemia Pada Kehamilan di Komunitas Ibu Hamil Puskesmas Gajahan Surakarta - Nurrofifah Luthfi Amjad; Taufik Eko Susilo; Amalia Faradila Rahim (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2024)
Anemia is caused by iron deficiency. Iron is a component that forms hemoglobin, where hemoglobin has the function of carrying oxygen throughout the body. During the pregnancy process, the body experiences very significant changes and requires many nutrients which are used for fetal growth, one of which is iron. This activity aims to provide education to pregnant women regarding anemia. The method used is education in the form of counseling by distributing leaflets to the community of pregnant women who take part in pregnancy exercises at the Gajahan Community Health Center. The results obtained from measuring increased understanding using pretest and post test questionnaires were an increase in understanding regarding anemia with an average pre test score of 14 and an average post test score of 82.